Being Bullied in Virtual Environments: Experiences and Reactions of Male and Female Students to a Male or Female Oppressor - Krämer, Nicole; Sobieraj, Sabrina; Feng, Dan; Trubina, Elisabeth; Marsella, Stacy (Frontiers in Psychology, 2018)
Bullying is a pressing societal problem. As such, it is important to gain a better understanding of the mechanisms involved in bullying and of resilience factors which might protect victims. Moreover, it is necessary to provide tools that can train potential victims to strengthen their resilience. To facilitate both of these goals, the current study tests a recently developed virtual environment that puts participants in the role of a victim who is being oppressed by a superior. In a 2 x 2 between-subjects experiment (N = 81), we measured the effects of gender of the oppressor and gender of the participant on psychophysiological reactions, subjective experiences and willingness to report the event. The results reveal that even when a male and a female bully show the exact same behaviour, the male bully is perceived as more threatening. In terms of gender of the victim, the only difference that emerged was a more pronounced increase in heart rate in males. The results were moderated by the personality factors social gender, neuroticism, and need to belong, while self-esteem did not show any moderating influence.